2019
DOI: 10.6023/cjoc201903052
|View full text |Cite
|
Sign up to set email alerts
|

Paired Electro-synthesis of Aryl Nitriles

Abstract: 曹志成 刘建超 褚有群 赵峰鸣 朱英红 * 佘远斌 * (浙江工业大学化学工程学院 杭州 310032) 摘要 采用循环伏安法(CV)和恒电流电解法(CCE)研究了对甲氧基苯甲醇(p-MeOC 6 H 4 CH 2 OH)电化学氧化氰化合成相 应芳腈化合物. 考察了水的体积分数、硫酸浓度、电解温度、电极材料、电流密度和溶剂等因素对该电化学氧化氰化 行为的影响. 结果显示, 以四丁基高氯酸铵(Bu 4 NClO 4)为电解质, 羟胺(HAM)为氮源, 在含 0.15 mol•L-1 H 2 SO 4 及 30% 水的 DMSO 体系中, 电流密度为 10 mA/cm 2 条件下恒温 60 ℃电解 8 h, 对甲氧基苯腈(p-MeOBN)的收率为 90%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Although the conductivity of the composite fiber decreased after drawing, the conductivity was still much higher than the conductivities of other conductive regenerated fibroin composite fibers reported in the literature. 13,20 Conclusions Biocompatible flexible conductive AgNW/fibroin composite fibers were fabricated from an AgNW/fibroin/FA solution by using a wet-spinning method. The conductivity of the composite fiber was as high as 5670 S/cm at an AgNW concentration of 29.1 wt%.…”
Section: Bulletin Of the Korean Chemical Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the conductivity of the composite fiber decreased after drawing, the conductivity was still much higher than the conductivities of other conductive regenerated fibroin composite fibers reported in the literature. 13,20 Conclusions Biocompatible flexible conductive AgNW/fibroin composite fibers were fabricated from an AgNW/fibroin/FA solution by using a wet-spinning method. The conductivity of the composite fiber was as high as 5670 S/cm at an AgNW concentration of 29.1 wt%.…”
Section: Bulletin Of the Korean Chemical Societymentioning
confidence: 99%
“…Cao et al reported a conductive and flexible silk-PANI-rGO (reduced graphene oxide) fabric by self-assembling of rGO and PANI on the surface of a silk fabric. 13 The composite silk fabric showed a good thermostability and low electrical surface resistance of 0.33 kΩ/cm. However, the conductivities of the abovementioned silk-based conductive fibers were low.…”
Section: Introductionmentioning
confidence: 96%
“…近年来, 电化学催化合成法作为绿色的合成策略, 成为有机合成领域的研究热点 [31][32][33][34][35][36][37][38][39] , 与传统有机合成相 比, 有机电化学合成使用电子作为清洁反应试剂, 避免 了有毒或危险的氧化剂和还原剂的使用, 减少了物质消 耗, 而且产品易分离、纯度高, 环境污染小; 同时, 电化 学合成反应通常在常温、常压下进行, 无需特殊的加热 和加压设备, 节约了能源, 降低了成本. 电化学有机合 成策略在 C-H 官能团化 [40] 、C-C 键构建 [41][42] 以及 C-Z (N, P, S, Se)键 [43][44][45][46] 的构建方面显现出显著的优势. 根据上述控制实验结果以及已有文献报道 [23,43] , 提 出电化学促进丙酮芳(烷)硒化反应的两种可能机理 (Scheme 3).…”
unclassified